2010
DOI: 10.1089/neu.2009.1226
|View full text |Cite
|
Sign up to set email alerts
|

Early and Sustained Increase in the Expression of Hippocampal IGF-1, But Not EPO, in a Developmental Rodent Model of Traumatic Brain Injury

Abstract: Pediatric traumatic brain injury (pTBI) is the leading cause of traumatic death and disability in children in the United States. Impaired learning and memory in these young survivors imposes a heavy toll on society. In adult TBI (aTBI) models, cognitive outcome improved after administration of erythropoietin (EPO) or insulin-like growth factor-1 (IGF-1). Little is known about the production of these agents in the hippocampus, a brain region critical for learning and memory, after pTBI. Our objective was to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Interestingly, experimental evidence supports the contention that IGF-1B is more neuroprotective than the IGF-1A isoform (Aperghis et al, 2004), and that unlike IGF-1, its product acts independently of the IGF-1 receptor (Armakolas et al, 2010;Dluzniewska et al, 2005;Gorecki et al, 2007;Siegfried et al, 1992). This independence from the IGF-1 receptor is particularly interesting in light of the fact that we had previously found that IGF-1 receptor mRNA levels decreased early after CCI (Schober et al, 2010) in the 17-day-old male rat hippocampus. In addition, studies in muscle devoid of IGF-1 receptor showed that overexpression of IGF-1B mRNA resulted in activation of pathways both in common and different from those resulting from administration of the IGF-1 mature peptide (Barton et al, 2010).…”
Section: Increased Igf-1b Mrna Variant Expression After Tbi 2081mentioning
confidence: 53%
See 4 more Smart Citations
“…Interestingly, experimental evidence supports the contention that IGF-1B is more neuroprotective than the IGF-1A isoform (Aperghis et al, 2004), and that unlike IGF-1, its product acts independently of the IGF-1 receptor (Armakolas et al, 2010;Dluzniewska et al, 2005;Gorecki et al, 2007;Siegfried et al, 1992). This independence from the IGF-1 receptor is particularly interesting in light of the fact that we had previously found that IGF-1 receptor mRNA levels decreased early after CCI (Schober et al, 2010) in the 17-day-old male rat hippocampus. In addition, studies in muscle devoid of IGF-1 receptor showed that overexpression of IGF-1B mRNA resulted in activation of pathways both in common and different from those resulting from administration of the IGF-1 mature peptide (Barton et al, 2010).…”
Section: Increased Igf-1b Mrna Variant Expression After Tbi 2081mentioning
confidence: 53%
“…IGF-1 promotes survival and proliferation of neurons and glia in the developing and adult brain (Aberg, 2010). In mature and immature rodents, either TBI (Li et al, 1998;Schober et al, 2010), or hypoxic ischemic injury (Beresewicz et al, 2010;Yan et al, 2006), increase brain IGF-1 expression. Indeed, blockade of endogenous IGF-1 activity in the adult brain worsened outcome after ischemia (Yan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations